Quiz Training Program through iSpring Suite 8.0 to Junior High School Teachers Tuban - Agus Wardhono; Anggia Kalista; Dyah Kurniawati; Ponco Bagyo Susilo (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
The purpose of this paper is for teachers to create their own teaching and evaluation materials using iSpring. This ability is very necessary considering that students are now a generation that is already familiar with the internet since they were born. While the teachers are a part of the digital immigrant generation, which was born before the internet developed rapidly. The method used in the form of training and mentoring was carried out by two English Education Lecturers and a Lecturer from the Faculty of Engineering which was attended by 36 junior high school teachers from both the city of Tuban and from other sub-districts around Tuban and held for four meetings. To find out the level of satisfaction of the training, participants were given a quiz and interview. The results of this training showed that most participants felt very enthusiastic, and could make their own material and evaluation in teaching English. After that they also managed to publish it in a format compatible with Android. This is very important because it is a combination of CALL (Computer Assisted Language Learning) and MALL (Mobile Assisted Language Learning), which means that this project uses computer devices and the results can be applied in the form of mobile (HP).